1996
DOI: 10.1139/x26-003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in growth, leaf abscission, and biomass associated with seasonal tropospheric ozone exposures of Populustremuloides clones and seedlings

Abstract: The effects of single-season tropospheric ozone (O3) exposures on growth, leaf abscission, and biomass of trembling aspen (Populustremuloides Michx.) rooted cuttings and seedlings were studied. Plants were grown in the Upper Peninsula of Michigan in open-top chambers with O3 exposures that ranged from 7 to 92 ppm-h. Depending on the genotype, total seasonal O3 exposure in the range of 50–92 ppm-h had negative impacts on stem, retained leaf, and root biomass accumulation and on diameter growth. Leaf abscission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
83
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(93 citation statements)
references
References 27 publications
9
83
1
Order By: Relevance
“…No significant ozone effect on height was found but in contrast for basal stem diameter a small (À3.2%) but significant negative effect (F 1,132 ¼ 11.24, p < 0.001) of ozone was found similar to that reported in a meta-analysis of forest tree ozone responses (Wittig et al, 2009), indicating that ozone exposure is likely to impact biomass yield. This will require further confirmatory analysis from longer-term studies, but suggests that Populus biomass yield is likely to be detrimentally affected by future increased ozone concentrations, which are consistent with previous reports (Bohler et al, 2007;Bortier et al, 2000;Karnosky et al, 1996;Wittig et al, 2009;Woo and Hinckley, 2005). Such decreases in productivity are likely to be related to decreased photosynthetic activity (Bortier et al, 2000;Coleman et al, 1995;Degl'Innocenti et al, 2007;Lorenzini et al, 1999) and reduced leaf area (Wittig et al, 2009).…”
Section: P Deltoides and P Trichocarpa Grandparents Show Contrastinsupporting
confidence: 78%
See 1 more Smart Citation
“…No significant ozone effect on height was found but in contrast for basal stem diameter a small (À3.2%) but significant negative effect (F 1,132 ¼ 11.24, p < 0.001) of ozone was found similar to that reported in a meta-analysis of forest tree ozone responses (Wittig et al, 2009), indicating that ozone exposure is likely to impact biomass yield. This will require further confirmatory analysis from longer-term studies, but suggests that Populus biomass yield is likely to be detrimentally affected by future increased ozone concentrations, which are consistent with previous reports (Bohler et al, 2007;Bortier et al, 2000;Karnosky et al, 1996;Wittig et al, 2009;Woo and Hinckley, 2005). Such decreases in productivity are likely to be related to decreased photosynthetic activity (Bortier et al, 2000;Coleman et al, 1995;Degl'Innocenti et al, 2007;Lorenzini et al, 1999) and reduced leaf area (Wittig et al, 2009).…”
Section: P Deltoides and P Trichocarpa Grandparents Show Contrastinsupporting
confidence: 78%
“…Symptoms range from accelerated senescence (Karnosky et al, 1996) and a decrease in growth rate (Karnosky et al, 1996Wittig et al, 2009), to foliar injury manifested as necrotic lesions analogous to those formed during the hypersensitive response (HR) . Concomitant with these symptoms is an up-regulation of defence and stress related genes and compounds (Conklin and Last, 1995;Lindroth, 2010;Ludwikow et al, 2004), and a down-regulation of photosynthetic components (Conklin and Last, 1995;Glick et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Based on much earlier examination of: (1) foliar symptoms on some 220 aspen clones representing 15 populations distributed across the natural range of aspen in the conterminous United States (Berrang et al, 1986); and (2) the subsequent growth and biomass responses of these clones planted in the Lake States region (Berrang et al, 1989;Karnosky et al, 1996), we believe that the five clones used in this study represented a very wide range of O 3 sensitivity that might be expected to occur within natural populations. Genotypic variation in response to O 3 among the clones (Karnosky et al, 1996(Karnosky et al, , 2003b .…”
Section: Discussionmentioning
confidence: 99%
“…Genotypic variation in response to O 3 among the clones (Karnosky et al, 1996(Karnosky et al, , 2003b . However, it is possible that clone 8L might respond negatively to higher O 3 concentrations that occurred during 2001e2003 within the Southwest/Midwest/central-mountain, mid-eastern US, southern Ontario/ Quebec/Nova Scotia in Canada, and within P. tremuloides populations in Mexico (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported the effects of elevated ozone exposure on individual plants and vegetation communities in field and controlled environments (Miller and Millecan, 1971;Karnosky and Steiner, 1981;Krupa and Manning, 1988;Karnosky et al, 1996;Heck et al, 1998). Research has identified numerous native species, such as Asclepias syriaca (common milkweed) and Prunus serotina (black cherry), useful in ozone bioindication surveys (Chappelka et al, 1997(Chappelka et al, , 1999aGunthardt-Goerg et al, 1999, 2000VanderHeyden et al, 2001;Yuska et al, 2003).…”
Section: Introductionmentioning
confidence: 99%